1977
DOI: 10.1002/jcu.1870050405
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variability in echocardiography

Abstract: High-quality echocardiograms were performed on 146 normal individuals whose ages ranged from 3 to 73 years (mean 27 years). Normal values for mitral diastolic excursion and E-F slope, the chamber dimensions of the right ventricle, left atrium, and left ventricle, the aortic root dimension, and thickness of the interventricular septum and left ventricular posterior wall were determined. Each tracing was then read independently by two experienced echocardiographers. The extent of interobserver variability was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 16 publications
1
12
1
Order By: Relevance
“…43 Studies on reproducibility and variability report that the percentage error for wall thickness is higher than that for left ventricular minor axis diameter. 42 -44 " 46 However, reproducibility of a wall thickness of 12 mm or more or of cardiac disease as compared to a wall thickness of 11 mm or less of normal subjects is much better, and the error is usually less than lO'fo. Although we do not have our own data on left ventricular wall thickness measurements in normal subjects, we have used 11 mm as the upper limit of normal, based on data from other reported studies.…”
mentioning
confidence: 99%
“…43 Studies on reproducibility and variability report that the percentage error for wall thickness is higher than that for left ventricular minor axis diameter. 42 -44 " 46 However, reproducibility of a wall thickness of 12 mm or more or of cardiac disease as compared to a wall thickness of 11 mm or less of normal subjects is much better, and the error is usually less than lO'fo. Although we do not have our own data on left ventricular wall thickness measurements in normal subjects, we have used 11 mm as the upper limit of normal, based on data from other reported studies.…”
mentioning
confidence: 99%
“…15 of the included 51 studies were published before the year 2000, while 36 were published from 2000 onwards. The oldest publication dates back to 1977 [12]. Twenty two studies were from reference populations in North or South America, 17 from European countries, 8 from Asia, 1 from the Middle East, 1 from Australia and 1 from north Africa (Egypt).…”
Section: Resultsmentioning
confidence: 99%
“…Nine of the studies presented the reference data of volunteers [12,14,22,36-41]. There were two studies sampling reference participants from wards [38,42], two studies sampled participants from a database(s) [43,44] and one study reported reference values of normal control group [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…' 6 For the assessment of the progression of the hypertrophy, thickness measurements obtained from M mode echocardiograms must be guided by cross sectional echocardiography, thus limiting the variability of these measurements. [26][27][28] Age, sex, familial incidence of hypertrophic cardiomyopathy, and medical treatment do not seem to influence the potential progression of hypertrophy. McKenna et al, using electrocardiography in a larger patient population, found not relation between these factors and the increase of electrocardiographic indices of left ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 98%